Pathogenicity of endophytic bacteria as entomopathogens against Spodoptera litura fabricius. (Lepidoptera: noctuidae) - Rahman, Afdil; Hamid, Hasmiandi; Resti, Zurai (CROPSAVER, 2023)
One of the biological controls of pest and plant disease is the use of enophytic bacteria. This study aimed to obtain endophytic bacterial from the root tissue of the shallot plant, which is potential as entomopathogens against the larvae of Spodoptera litura. This research was arranged in a completely randomized design (CRD) with nine treatments consisting of eight endophytic bacteria (isolation from shallot root tissue) and one control with three replications. Parameters observed were larval mortality, percentage of normal and abnormal pupae formed, percentage of normal and abnormal imago formed. The results showed that the bacteria of Serratia marcescens JB1E3 and Bacillus cereus P.14 caused the highest mortality in the larval phase, while Serratia marcescens ULG1E4 and Bacillus sp. SJI showed a long-term (latent) effect, resulting in no formation of pupa and imago of Spodoptera litura.